2016
DOI: 10.1093/europace/euw191
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of silent cerebral infarctions after catheter ablation of atrial fibrillation utilizing the second-generation cryoballoon

Abstract: Pulmonary vein isolation utilizing second-generation CBs carries a negligible risk of symptomatic CIEs; however, it includes a comparable risk of asymptomatic CIEs as in the previous similar reports using the first-generation CB. Radiofrequency applications in addition to the CB within the LA were the only predictor of this adverse effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 24 publications
4
30
0
Order By: Relevance
“…In AXAFA-AFNET 5, MoCA scores were similar in women and men. The number of study patients with acute brain lesions after ablation (∼25%) was in line with previous publications 19 , 20 and without significant differences in women and men. In light of this relatively high percentage of acute brains lesions, the observation that in both women and men the presence of at least mild cognitive dysfunction according to the MocA test decreased in a similar manner from 32% and 30%, respectively to 23% at the end of follow-up is reassuring but may be related to repetitive testing.…”
Section: Discussionsupporting
confidence: 91%
“…In AXAFA-AFNET 5, MoCA scores were similar in women and men. The number of study patients with acute brain lesions after ablation (∼25%) was in line with previous publications 19 , 20 and without significant differences in women and men. In light of this relatively high percentage of acute brains lesions, the observation that in both women and men the presence of at least mild cognitive dysfunction according to the MocA test decreased in a similar manner from 32% and 30%, respectively to 23% at the end of follow-up is reassuring but may be related to repetitive testing.…”
Section: Discussionsupporting
confidence: 91%
“…The incidence of SCILs in the CBA and HBA groups was 21.5% and 13.8%, respectively, and that in the CBA group was similar to that reported in recent studies with a CB‐based AF ablation . To the best of our knowledge, there have been no previous studies reporting the incidence of silent cerebral embolisms after radiofrequency HBA of AF.…”
Section: Discussionsupporting
confidence: 87%
“…Balloon‐based AF ablation, as well as radiofrequency catheter‐based AF ablation, has a potential risk for periprocedural embolic complications. Symptomatic embolisms, including ischemic strokes, transient ischemic attacks (TIAs), and systemic emboli, after cryoballoon ablation (CBA) of AF are rare occurrences, while silent cerebral emboli detected by brain magnetic resonance (MR) imaging are relatively common, and have been reported to be observed in 4.3% to 50% of patients undergoing CBA . So far, limited data are available on the incidence of symptomatic and silent embolisms after radiofrequency HotBalloon ablation (HBA) of AF …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,7,33 Increased incidence of SCE has been reported with reinsertion and application of a previously withdrawn cryoballoon, multielectrode catheter use for additional left atrial mapping, and transient coronary air embolism. 34 Additional radiofrequency ablation within the left atrium in patients undergoing nonpulmonary vein isolation ablation was an independent risk factor for cerebral ischemic events in a study by Nakamura et al 35 In a very recent metaanalysis published, uninterrupted DOAC was found to of similar bleeding events with comparison to minimally interrupted DOAC and also mirrored our ndings of lesser SCE. 36 However, this study did not explore the procedural aspects, specially relation to use of Heparin and ACT.…”
Section: Predictors Of Silent Cerebral Eventssupporting
confidence: 73%